Band formation at interfaces between N-heteropolycycles and gold electrodes [research data] - Stein, Arnulf; Rolf, Daniela; Lotze, Christian; Günther, Benjamin; Gade, Lutz H.; Franke, Katharina J.; Tegeder, Petra (Universität, 2024)
Underlying data for figures in the paper "Band Formation at Interfaces Between N-Heteropolycycles and Gold Electrodes" (2021-01-13)
Finanziert durch: Deutsche Forschungsgemeinschaft: SFB 1249: N-heteropolycycles as functional materials: 281029004-SFB 1249, Project B06
Gesehen am 12.02.2024
Keywords: Forschungsdaten; Datenbank